Relative clause attachment in Mandarin Chinese: insights from classifier-noun agreement - Liu, Fengming; Lin, Chien-Jer Charles (Frontiers in Language Sciences, 2024)
This study investigated relative clause attachment ambiguity in Mandarin Chinese, with the manipulation of classifier-noun agreement. Two self-paced reading experiments were conducted to examine people's attachment preferences in comprehension. Experiment 1 revealed a significant effect of classifier-noun agreement in offline comprehension: there was an increase in selecting the high-attachment noun (NPhigh) as the relative clause (RC) attachment site when the classifier agreed with NPhigh, whereas there was a decrease in selecting NPhigh when the classifier agreed with the low-attachment noun (NPlow). Online processing results supported this effect, showing that classifiers guide comprehenders' expectations by pre-activating semantic features of the upcoming noun, thus modulating RC attachment preferences. Experiment 2 introduced semantic compatibility between the RC and potential attachment nouns as an additional disambiguating cue, revealing a reliable prediction effect for the upcoming noun. Although the classifier's prediction effect was diminished, it remained influential in this condition. Additionally, the study revealed a dynamic pattern of RC attachment preferences, characterized by an early low-attachment during initial online processing, transitioning to a high-attachment preference in later online and offline stages, particularly favoring NPhigh as the attachment site. This study highlights the complexity of relative clause attachment in Mandarin, demonstrating the significant predictive roles of classifier-noun agreement and semantic compatibility.